Alimentação de espécies de peixes dominantes em arrastos de fundo na Baía de Camamu, BA - Nascimento, Carla Pereira (2011)
THE objective of this study was to analyze the diet of Sphoeroides testudineus, S. greeleyi and Cyclichthys spinosus, test the alimentary overlap in these species, and the possible influences of environmental, temporal and/or body size of the individuals on the diet of the species. Fishes were caught by otter trawl between July 2003 and December 2004 in eight sites at the Camamu Bay, where each site was 2,5km distant. 50 specimens of each specie were measured and eviscerated and their digestive tracts were analyzed. The items were identified to the lowest taxonomic level possible and grouped in categories. The frequency of occurrence and volumetric frequency were calculated and combined into an Index of Alimentary Importance. The frequency of occurrence and volumetric frequency were calculated and combined into an Index of Alimentary. The alimentary overlap and diversity of items were calculated for each study site, period hydrologic of cycle and size classes. Furthermore, the repletion degree of the digestive tracts was verified. A total of 45 items were identified, and among them plant was the most frequent in the diet of the three species, which were characterized as omnivore in the younger stages of the lifecycle, changing to carnivore with tendency to feed on hard items in the older stages of development. Few individuals were found with empty digestive tract. There was a high diet overlap between in the genera Sphoeroides, and between S. testudineus and C. spinosus, which does not imply in competition for resources, possibly due to the trophic opportunism of these species. The higher alimentary diversity was in the sites 3, 4 e 6, which are located in the less disturbed region. Furthermore, there are differences in the use of the items between wet and dry season.